The business of managing nurses' substance‐use problems. Issue 1 (15th November 2019) - Ross, Charlotte A.; Jakubec, Sonya L.; Berry, Nicole S.; Smye, Victoria
Abstract: Nurses' experiences in, and the overall effectiveness of, widely used alternative‐to‐discipline programs to manage nurses' substance‐use problems have not been adequately scrutinized. We uncovered the conflicted official and experiential ways of knowing one such alternative‐to‐discipline program in a Canadian province. We explicated this conflict through an institutional ethnography analysis. Ethnographic data from interviews with 12 nurses who were enrolled in an alternative‐to‐discipline treatment program and three program administrators, as well as institutional texts, were analyzed to explore how institutional practices and power relations co‐ordinated and managed nurses' experiences. Analysis revealed the acritical acceptance of a standardized program not based on current norms of practice. Potential and actual conflicts of interest, power imbalances, and prevailing corporate interests were rife. Nurses were not afforded the same rights to quality ethical health care as other citizens. 'Expert' physicians' knowledge was privileged while nurses' knowledge was subordinated. Conclusions were that regulatory bodies cannot rely on the taken‐for‐granted standardized treatment model in widespread use. Individualized treatment alternatives reflecting current, scientific evidence must be offered to nurses, and nurses' knowledge, expertise, and experiences need to be included in decision‐making processes in these programs.